ANALISIS TRADISI BUKHOREN SEBAGAI PERAYAAN MAULID NABI MUHAMMAD SAW: PERSPEKIF ZIKIR DAN NILAI-NILAI PENDIDIKAN ISLAM DI PONDOK PESANTREN AL-FITHORH JEJERAN: (Analysis of the Bukhoren Tradition as a Celebration of the Prophet Muhammad's Birthday: The Perspective of Zikir and Islamic Educational Values ​​at the Al-Fithorh Jejeran Islamic Boarding School) - Zuhaili Zulfa (Raqib: Jurnal Studi Islam, 2025)
This study aims to examine the implementation of the Bukhoren activities and the meanings embedded in this tradition. The method used is qualitative-descriptive research, which allows the researcher to deeply explore data related to the practices and values present in Bukhoren activities. The findings reveal that Bukhoren, as part of the religious traditions of the community, holds profound significance in various dimensions of Muslim life. This tradition reflects the love for Prophet Muhammad (peace be upon him) through practices such as zikir (remembrance of Allah), the recitation of the Shahih Al-Bukhari text, prayers, and salawat, which form part of the celebration of the Prophet Muhammad’s (peace be upon him) birth. Besides serving as a means of worship and spiritual reinforcement, Bukhoren also plays an educational role in preserving Islamic teachings and fostering Islamic brotherhood within the community.  The conclusion of this study emphasizes that the Bukhoren tradition not only sustains religious values but also serves as a tool to build social solidarity and perpetuate Islamic cultural heritage across generations. Thus, Bukhoren is not merely a religious ritual but also a medium for Muslims to draw closer to Allah and emulate the noble character of Prophet Muhammad (peace be upon him).